Attitude, Risk Perception and Social Factor as Predictors of Intention to Pursue a Master’s Degree: An Application Planned Behavior Theory - Chand, Prayukta; Maharajan, Urbashi; Rana, Bivek (MVIC Journal of Management and Information Technology, 2025)
Pursuing a master’s degree has become both a social and academic trend among youths facing career uncertainty and social competition. Credential devaluation has contributed to viewing the master’s as the new bachelors. In the United States, master’s enrollment increased by 15 percent between 2020 and 2030 and is projected to grow by 17 percent between 2019 and 2030. China reported more than 4.74 million postgraduate exam takers in 2023. Nepal mirrors the rising interest, yet Tribhuvan University, which enrolls more than 70 percent of the country’s university students, recorded a nearly 3 percent decline in enrollment. The decline is linked to growth in outbound study, with a 42.3 percent increase in Nepali students going abroad for master’s programs between late 2022 and 2023, making Nepal one of the fastest-growing sources of international graduate students in Asia. Although regional studies have examined higher education intention using the Theory of Planned Behavior, evidence from Nepal especially within the social sciences—remains scarce and often relies on proxy measures of intention. In Nepal, subjective norm and perceived behavioral control may have limited predictive validity because of economic constraints and deeply embedded collectivist norms. This study addresses contextual and methodological gaps by developing and validating a new intention scale for Nepali undergraduates and by applying a partial Theory of Planned Behavior framework that focuses on attitude, risk perception, and social factors. The study asks whether the new scale is valid and reliable and how these three predictors influence intention to pursue a master’s degree in Nepal. Limitations include the use of a partial Theory of Planned Behavior model, potential social desirability in self-reports, and the focus on intention rather than observed enrollment behavior.